Proposta de um vocabulário semântico para descobrir serviços na internet das coisas - Lima, Mayka de Souza (2016)
The Internet of Things is a network infrastructure that is based on communication protocols, domains and applications connecting physical objects, such as sensors or remote devices through wireless communications. In order for smart objects perform their functions when connected to the Internet using web resources, it is necessary that the communication interfaces can treat the search for a specific service requested by the user accurately. The search for this service gives with a clear and objective semantics used in the vocabulary for the request process. In some research cited in the work the use of semantic vocabularies in web services, has some problems that persist in the clear detection of these services. These papers that perform search services were analyzed and correlated their positive and negative aspects about the semantics used in the vocabulary and its application in the IoT. In this manner, to achieve a process of discovery services, this paper presents a semantic vocabulary that performs discovery services on the Internet of things. The vocabulary built was implemented in an application that performs the communication of an application of best price, which has a market server and a fridge that seek a particular service. After implementation the vocabulary search process was simulated in Cooja Simulator Contiki operating system and used the language JSON (JavaScript Object Notation) based on the discovery code, simple language and widely used for web applications. After the simulation, we analyzed the communication services exchanged between the Best Price server and Market applications and fridge, getting the memories of sensor nodes failed to perform the sending of the semantic vocabulary response services because of a size limitation of ROM (Read Only memory) of the simulated sensor nodes.